DEVELOPING LEARNING MATERIALS OF PEACEFUL SHORT STORY WRITING TO INCREASE THE STUDENTS’ CREATIVITY FOR THE ELEVENTH GRADERS OF SENIOR HIGH SCHOOL - Putro, AgelgaraKusumo; Priyatni, Endah Tri; Pratiwi, Yuni (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Peace-loving short stories have a great opportunity in boosting a tolerant character for the nation’s next generation. This character is very important to be developed in response to the lack of tolerance in the current era of information disclosure. This mechanism is carried out by integrating the load of tolerance characters in learning to write short stories. Through learning to write short stories, students can show a tolerant attitude in developing story ideas, characters, characterizations, conflicts, and storylines. This study aims to develop peaceful short story text teaching materials to strengthen the peace-loving character. Apart from internalizing the peace-loving character, creativity also needs to be trained in students to prepare them for the time being. Creativity is a basic skill needed by the students to be ready to compete in the 21stcentury. This research uses the research design and development model of Borg & Gall. Based on the validation test, this teaching material is categorized as valid and suitable for use. The form of assignment in this teaching material is also systematically designed to train aspects of creativity which include originality, elaboration, and flexibility. Efforts are also made to develop stories in this teaching material to expose the peace-loving character. The aspects of peace-loving character that are exposed in this teaching material include tolerance, empathy, sympathy, equality, and altruism. Keywords:Learning materials, short stories, peace love, creativity